STRATEGI PENINGKATAN KINERJA PEMERINTAH KECAMATAN DI KABUPATEN KUANTAN SINGINGI (STUDI DI KECAMATAN CERENTI) - Yulanda Lestari; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Based on data performance appraisal of the dstrict state civil servanst the Kuantan Singingi experienced a decline, Cerenti sub-district government one of the institutions under the Kuantan Singingi district government also found a decrease in employee performance. Therefore it is necessary to study how stratehies to improve the performance of these employees. Performance improvement strategy is a method used by agencies or organizations to provide the best service according to the needs of the community. This study aims to determine the strategies used by the Cerenti sub-district government in improving its performance, by increasing the number of employees according to needs. And identifying factors that hinder the strategy of improving the performance of the Cerenti sub-district government. This research user descriptive qualitative methods. This method uses the theory of performance improvement strategies from Wibowo wit indicators of educations and training, motivation, and incentives. From the result of the study it was found that the strategy of improving the performance of the Cerenti sub-district government of Cerenti was not exactly, viewed from a number of indicators one of which is limited edication and training makes not all employess can take part in the training. And  there inhibiting factors in the from of limited facilities and infrastructure, limited human resource, limited ability of employees.  Keywords:Strategy, Improvement, Employee performance